Using LEGO® Mindstorms and MATLAB in curriculum design of active learning activities for a first-year engineering computing course - Tronchin, Olivia (My University, 2019)
The goal of this research project was to investigate the feasibility of implementing a programmable robot (LEGO Mindstorm) combined with a computer program (MATLAB) into MacEwan's Engineering Computer Programming (ENCP 100) curriculum as a hands-on active learning tool.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.